Changes in taste reactivity to intra-oral hypertonic NaCl after lateral parabrachial injections of an alpha(2)-adrenergic receptor agonist - Andrade, Carina A. F. [UNESP]; Andrade-Franze, Glaucia M. F. [UNESP]; De Luca, Laurival A. [UNESP]; Johnson, Alan Kim; Menani, José Vanderlei [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Bilateral injections of moxonidine, an alpha(2)-adrenoceptor and imidazoline receptor agonist, into the lateral parabrachial nuclei (LPBN) enhance sodium appetite induced by extracellular dehydration. In the present study, we examined whether LPBN moxonidine treatments change taste reactivity to hypertonic NaCl solution administered into the mouth by intra-oral (IO) cannula. Male Holtzman rats prepared with IO and bilateral LPBN cannulas received subcutaneous injections of furosemide (FURO; 10 mg/kg) and captopril (CAP; 5 mg/kg) to induce hypovolemia with mild hypotension and an accompanying salt appetite and thirst before testing the taste reactivity to oral infusions of 0.3 M NaCl (1.0 ml/min). In the first experiment 45 min after subcutaneous injections of FURO + CAP or vehicle, moxonidine was bilaterally injected into the LPBN, and then 15 min later both bodily and oral-facial ingestive and rejection responses to 0.3 M NaCl delivered through the IO cannula were assessed. Both LPBN vehicle and moxonidine treated rats showed increased ingestive and decreased rejection responses to the IO hypertonic solution. The 100.3 M NaCl infusion-evoked ingestive and rejection taste related behaviors were comparable in the LPBN vehicle- vs. the LPBN moxonidine-injected groups. In a second experiment, rats received the same FURO + CAP treatments and LPBN injections. However, beginning 15 min after the LPBN injections, they were given access to water and 0.3 M NaCl and were allowed to consume the fluids for most of the next 60 min with the free access intake being interrupted only for a few minutes at 15,30 and 60 min after the fluids became available. During each of these three brief periods, a taste reactivity test was conducted. on the three taste reactivity tests rats that received LPBN vehicle injections showed progressive declines in ingestive responses and gradual increases in rejection responses. However, in contrast to the LPBN vehicle treated rats, animals receiving bilateral injections of LPBN moxonidine maintained a high number of ingestive responses and a low number of rejection responses throughout the test period even in spite of evidencing substantial water and 0.3 M NaCl consumption during the periods of free access. The results suggest that after alpha(2)-adrenoceptor agonist delivery to the LPBN the acceptance of 0.3 M NaCl is sustained and the negative attributes of the solution are minimized. The maintained positive rewarding qualities of 0.3 M NaCl are likely to account for why LPBN moxonidine treated rats show such a remarkable salt appetite when assayed by the volume of hypertonic 0.3 M NaCl consumed. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Palatability; Taste; Adrenoceptors; Thirst; Sodium appetite; Hindbrain